CHINA’S MARKET EXPANSION AND IMPACTS ON NIGERIA’S TEXTILE INDUSTRY - Osondu-Oti, Adaora (Journal of Contemporary International Relations and Diplomacy, 2021)
This study analyses the various ways in which China’s market expansion impacts Nigeria’s textile industry. Two major surviving textile firms in Nigeria were studied: Sunflag Textile Manufacturing Company and the United Nigerian Textile Manufacturing Company. The study made use of documentary research and a qualitative case study, where an interview was employed as the research tool. Global economic integration/trade liberalization formed the theoretical basis for analysis. Findings reveal that China’s market expansion driven by globalisation impacts significantly on Nigeria’s textile industry. For instance, the influx of Chinese cheap textiles (80 per cent of textiles in the Nigerian market today are imported from China) and the re-export of textiles imported from China by neighbouring states such as the Benin Republic to Nigeria through smuggling has led to an almost total collapse of Nigeria’s textile industry. China has also taken advantage of the country’s huge infrastructure deficit and government neglect of the textile sector to replicate Nigerian unique Wax print known as Ankara, thereby displacing local producers. Thus, the once-thriving manufacturing textile sector has become moribund as Chinese textiles take over the Nigerian market. The study recommends that the Nigerian government should support (financially) the distressed/collapsed firms and also upgrade the country’s infrastructure particularly the power sector for the remaining textile firms to survive and compete successfully in a globalised world.